Speaking constraints faced by senior high school students and their efforts to overcome the constraints - Trissuci Ramiza; Bukhari Daud (Universitas Syiah Kuala, 2017)
Speaking skill is one of the important skills in English that should be mastered by learners as a basic medium to communicate or interact with each other. However, the students often face difficulties in speaking. Therefore, the objectives of this study are to investigate the problems of speaking faced by senior high school students in SMA Negeri 1 Sabang and also to find out the efforts done by the students in overcoming their problems. The subject of this study consists of 30 students selected randomly from all of the second year grade students in SMA Negeri 1 Sabang. The method used is descriptive qualitative which is the data collections are questionnaire and interview. After finding out the result, the writer described the questionnaire’s results in form of graphics, while the interview’s results are described in a narration form. The result of the study shows that all of the students faced the speaking difficulties, but mostly the constraints are different one another. They also have done efforts to cope with the problems.